ANALISIS BEBAN KERJA BERDASARKAN WAKTU KERJA KARYAWAN PADA UNIT PEMUPUKAN DI PT.TANJUNG BUYU PERKASA PLANTATION KALIMANTAN TIMUR - Alvieyan Nur Ari Pratama (JURNAL AGRIMENT, 2019)
Palm oil (Elaeis Guineensis Jack.) Is one of the mainstay plantation commodities in Indonesia. Palm oil agribusiness is one of the few industries that is Indonesia's competitive advantage to compete at the global level. Based on research that has been done the highest average productive work time is obtained at KP 3, 4, 5, 6, 9, and KP 10 which is equal to 48.8%, and the lowest productive time is obtained at KP 7 and KP 8 which is 47.4% with unproductive time the highest is obtained by KP 3 and KP 4 which is 12.5%, and the lowest unproductive time is obtained by KP 9 and KP 10 which is 9.6%, while the highest personal time is obtained by KP 5 and KP 6 which is 42.9% and the lowest personal time is obtained by KP 3 and KP 4 which is 38.5%. The overall time of employees between Earning time and personal time didn’t making a significant change this is due to KP at PT. Tanjung Buyu Perkasa Plantation works in teams, if between 1 or more than 1 employee in the process of working slowly it will hamper the work process of other employees. The calculation of the workload per year for the entire KP is below 1 with information on the underload, which means that the workload of the entire KP is relatively low because this is due to the flat land and fertilizer worker doing his work by teamwork.